Métiers and Socioeconomics of the Hellenic Small-Scale Sea Cucumber Fishery (Eastern Mediterranean Sea) - Kyriakoula Roditi; Chryssanthi Antoniadou; Chrysoula Apostologamvrou; Dimitris Vafidis (Fishes, 2025)
Holothurian fisheries have become a prominent métier in the Mediterranean due to increasing worldwide demand for sea cucumbers. In these newly explored grounds, their fisheries are poorly understood, especially considering the applied tactics and socioeconomics of the harvesting fleet. This study examines the small-scale holothurian (Holothuria) fishery métiers and associated socioeconomics in the Hellenic Seas—a main Mediterranean fishery ground. Holothuria fishing licenses increased in 2020 and stabilized (130) in the next years. Holothuria poli and H. tubulosa are the target species, caught by hand, using the surface air supply method or free diving. Most fishermen harvest holothurians close to the port of origin, and only the fleet from Kalymnos exploits remote grounds over the Greek territory. According to harvesting tactics, three economically viable métiers are practiced; however, shifting to alternative fishery resources is necessary to grant annual income. Sea cucumbers are sold fresh from fishermen to merchandisers who process the catch into final products (trepang) and export them. For most fishermen (64.7%), fishing for holothurians is the main occupation, gaining a highly variable monthly income (EUR 700 to 4000). The presented results refine the métiers and associated economics of an active holothurian fishery fleet, providing essential information for the viability of coastal fishery societies.